IVIG Treatment Response and Age are Important for the Prognosis of Pediatric Immune Thrombocytopenia - Min Gi Sakong; Ji Hoon Park; Sang Beom Son; Yu Kyung Kim; Jae Min Lee (The Korean Society of Pediatric Hematology-Oncology, 2022)
Background : : This study aimed to identify chronicity predictors of pediatric primary immune thrombocytopenia (ITP). Methods : : This study retrospectively reviewed the medical records of patients with primary pediatric ITP admitted to a tertiary medical center between 2010 and 2021. Forty-five patients with a platelet count <20,000/µ;L at the time of diagnosis who were treated with intravenous immunoglobulin (IVIG) were enrolled in this study. Results : : According to the disease phase, 28, 6, and 11 patients were classified into the newly diagnosed (ND), persistent, and chronic groups, respectively. The number of patients over 6 years of age was significantly higher in the chronic group than in the ND and persistent groups. After 14 days of IVIG treatment, more patients had a complete response in the non-chronic groups than in the chronic group. In univariate analysis of risk factor for chronic ITP, age 6 years or older and IVIG dose <2 g/kg were found to be risk factors for chronic ITP, and these two factors were also confirmed as significant risk factors in multivariate analysis. Conclusion : : In conclusion, in our study, patients over 6 years of age, and those who received IVIG doses less than 2 g/kg were more likely to progress to chronic ITP.